2017
DOI: 10.1117/12.2261597
|View full text |Cite
|
Sign up to set email alerts
|

Variable input observer for state estimation of high-rate dynamics

Abstract: High-rate systems operating in the 10 μs to 10 ms timescale are likely to experience damaging effects due to rapid environmental changes (e.g., turbulence, ballistic impact). Some of these systems could benefit from real-time state estimation to enable their full potential. Examples of such systems include blast mitigation strategies, automotive airbag technologies, and hypersonic vehicles. Particular challenges in high-rate state estimation include: 1) complex time varying nonlinearities of system (e.g. noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Structural health monitoring of systems experiencing harsh extreme environments is a complex task. Research has shown these systems include multiple system complexities such as highly nonlinear and nonstationary behaviors [2] for which fixed observers are difficult to apply [3] An alternative is to use adaptive observers, but at the cost of slower convergence rates. Literature focuses on accelerating the convergence of adaptive observers, with the vast majority of efforts on the state estimation function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural health monitoring of systems experiencing harsh extreme environments is a complex task. Research has shown these systems include multiple system complexities such as highly nonlinear and nonstationary behaviors [2] for which fixed observers are difficult to apply [3] An alternative is to use adaptive observers, but at the cost of slower convergence rates. Literature focuses on accelerating the convergence of adaptive observers, with the vast majority of efforts on the state estimation function.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,6] for instance. Instead, the authors have proposed to use an adaptive input space to accelerate convergence, a strategy termed VIO [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation